2016
DOI: 10.1088/0964-1726/25/11/115010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corrosion induced surface morphology changes on ultrasonically monitored corrosion rates

Abstract: Corrosion rates obtained by very frequent (daily) measurements with permanently installed ultrasonic sensors have been shown to be highly inaccurate when changes in surface morphology lead to ultrasonic signal distortion. In this paper the accuracy of ultrasonically estimated corrosion rates (mean wall thickness loss) by means of standard signal processing methods (peak to peak-P2P, first arrival-FA, cross correlation-XC) was investigated and a novel thickness extraction algorithm (adaptive cross-correlation-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Another problem that it will be important to address in some cases is corrosion causing changes in the roughness profile of the back wall and hence in the echo shape as well as its arrival time. 32 It has been shown that it is possible to obtain reliable thickness changes even in the presence of varying roughness profiles, 33 but the changing nature of the back wall echo will make it impossible to detect small defects from changes in the back wall signal or the ratio of successive signals. Therefore, alternative compensation schemes will have to be devised.…”
Section: Results Using Back Wall Echo Ratiomentioning
confidence: 99%
“…Another problem that it will be important to address in some cases is corrosion causing changes in the roughness profile of the back wall and hence in the echo shape as well as its arrival time. 32 It has been shown that it is possible to obtain reliable thickness changes even in the presence of varying roughness profiles, 33 but the changing nature of the back wall echo will make it impossible to detect small defects from changes in the back wall signal or the ratio of successive signals. Therefore, alternative compensation schemes will have to be devised.…”
Section: Results Using Back Wall Echo Ratiomentioning
confidence: 99%
“…The peaks of this autocorrelated signal were used to determine the speed by assuming a constant plate thickness of 8 mm, and dividing by the time difference between those peaks. Autocorrelation was used instead of a simple timedomain analysis as it provides better signal-to-noise ratios and is less prone to errors arising from dispersion or signal distortion [25], [26].…”
Section: A Longitudinal Wave C-scansmentioning
confidence: 99%
“…Finally, Ref. [37] proposes a non-standard approach based on cross-correlation, but, instead of performing the correlation with the transmitted signal, they correlate a back-wall echo with a reference signal that has been modified using an iterative algorithm that also involves cross-correlations. Thus, this approach achieves wall-thickness estimations (below 1 µm) on ultrasonic signals.…”
Section: Related Workmentioning
confidence: 99%